2002
DOI: 10.1103/physrevlett.88.197203
|View full text |Cite
|
Sign up to set email alerts
|

Colossal Magnetoresistance is a Griffiths Singularity

Abstract: It is now widely accepted that the magnetic transition in doped manganites that show large magnetoresistance is a type of percolation effect. This paper demonstrates that the transition should be viewed in the context of the Griffiths phase that arises when disorder suppresses a magnetic transition. This approach explains unusual aspects of susceptibility and heat capacity data from a single crystal of La0.7Ca0.3MnO3.The term "colossal magnetoresistance" (CMR) has commonly been used to describe the very large,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
256
3
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(290 citation statements)
references
References 30 publications
28
256
3
3
Order By: Relevance
“…The down turn in the magnetic susceptibility at temperatures above T C for the sample with x ¼ 0.20 is the signature of the "Griffiths phase." 22 The deviation from Curie-Weiss law in the PM region is due to the presence of FM clusters within the PM region.…”
Section: Resultsmentioning
confidence: 99%
“…The down turn in the magnetic susceptibility at temperatures above T C for the sample with x ¼ 0.20 is the signature of the "Griffiths phase." 22 The deviation from Curie-Weiss law in the PM region is due to the presence of FM clusters within the PM region.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies concluded that the local distortion revealed by an anomalous thermal expansion between the Curie-Weiss transition temperature T C and a higher temperature T * pointed towards the presence of ferromagnetic clusters or polaronic interactions being responsible for the electrical conduction [8][9][10]. The presence of clusters in the paramagnetic (PM) region was associated with signature magnetic behavior observed in Griffiths phases [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The intra-cluster magnetic ordering temperature above experimentally observable bulk T C varies depending on the size of the cluster and therefore there is a spectrum of T C below the characteristic Griffiths temperature, T G . Though the existence of such a magnetic phase due to quenched disorder has been discussed in connection with giant magnetoresistance behavior of manganites [6,[11][12][13], non-Fermi liquid behavior in f-electron systems [14,15], and dilute magnetic semiconductors [16] as well as for a Tb-based intermetallic compound [7], it is believed that the experimental evidence in favor of the existence of Griffiths phase is still inadequate [17].…”
Section: We Now Focus On the Behavior Of 12k-transition In The Low Fimentioning
confidence: 99%